Active schedules and a new hybrid genetic algorithm for the job shop scheduling problem - Nguyen, Huu Mui (H. : ĐHQGHN, 2017)
Active schedules and a new genetic algorithm for solving job shop scheduling problein are presented in this paper. In the proposed method, a chromosome representation of the problem is natural numbers, the GT algorithm is used to generate a set of active solutions, the mutation is implemented on the all machines concurrently. Especially, we propose a new crossover operator that combines the unifurm crossover operator with GT algoithm and is implemented on 3 parents. The approach was tested on a set of benchmark programs and compared with other approaches.The computation results validated the effectiveness of the proposed algorithm.